The Effect of Polyvictimization on the Development of Moral Disengagement and Effects on Violent offending in Adulthood: Emotional and Cognitive Mediation Effects - Wojciechowski, Thomas (Victims & offenders, 2021)
Polyvictimization, moral disengagement, impulse control, and hostility are all risk factors for violent offending. The present study tested a multiple mediation model to identify pathways leading from polyvictimization early in life to violent offending risk in adulthood. The Pathways to Desistance data were used in analyses. Group-based trajectory modeling was utilized to identify developmental heterogeneity in moral disengagement during adolescence. Generalized structural equation modeling was used to estimate multiple mediation pathways. Results indicated that a two-group moral disengagement model best fit the data. Increased polyvictimization scores at baseline predicted increased risk for violent offending in adulthood. This relationship was mediated by differential development of moral disengagement, hostility in adulthood, and impulse control in adulthood. The full path running from polyvictimization to differential development of moral disengagement to impulse control to violent offending was found to be significant. These findings indicate that polyvictimization may lead to high and chronic levels of moral disengagement, which may then lead to diminished impulse control, and that this entire sequence may increase violent offending risk.